Improving osteoinduction and osteogenesis of Ti6Al4V alloy porous scaffold by regulating the pore structure - Wang, Chao; Wu, Jie; Liu, Leyi; Xu, Duoling; Liu, Yuanbo; Li, Shujun; Hou, Wentao; Wang, Jian; Chen, Xun; Sheng, Liyuan; Lin, Huancai; Yu, Dongsheng (Frontiers in Chemistry, 2023)
The titanium alloy scaffold with a porous structure has attracted much attention in bone defect repair. However, which pore structure is more beneficial to bone defect repair is controversial. In the present research, the Ti6Al4V alloy porous scaffolds with gradient pore sizes were designed and fabricated. The microstructure characterization, mechanical properties tests, in vitro and in vivo experiments had been performed to systematically evaluate the effect of pore size on osteoinduction and osteogenesis. The results revealed that the contact angle with water, compressive strength and elastic modulus of the Ti6Al4V alloy porous scaffolds decreased gradually with the increasing of pore size. However, there were obvious drops when the pore size of the porous scaffold located around 600 μm. As the pore size increasing, the proliferation and integrin β1 of RAW 264.7 macrophages seeded on Ti6Al4V alloy porous scaffolds increased firstly, reaching a maximum value at pore size about 600 μm, and then decreased subsequently. The proliferation, integrin β1 and osteogenic gene-related expressions of Bone marrow mesenchymal stem cells (BMSCs) seeded on Ti6Al4V alloy porous scaffolds with different pore sizes all exhibited the similar variations which rose with increased pore size firstly, obtaining the maximum value at pore size about 600 μm, and then declined. The in vivo experiments confirmed the in vitro results, and the Ti6Al4V alloy porous scaffold with a pore size of 600 μm possessed the better capability to induce new bone formation. Therefore, for the design of Ti6Al4V alloy with regular porous scaffold, the surface morphology, porosity, strength, and elastic modulus should be considered systematically, which would determine the capability of osteoinduction and osteogenesis.